2014
DOI: 10.1371/journal.pone.0094435
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Chinese Indigenous Goats and the Special Geographical Structure in the Southwest China as a Geographic Barrier Driving the Fragmentation of a Large Population

Abstract: BackgroundChina has numerous native domestic goat breeds, however, extensive studies are focused on the genetic diversity within the fewer breeds and limited regions, the population demograogic history and origin of Chinese goats are still unclear. The roles of geographical structure have not been analyzed in Chinese goat domestic process. In this study, the genetic relationships of Chinese indigenous goat populations were evaluated using 30 microsatellite markers.Methodology/Principal FindingsForty Chinese in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
5
23
2
1
Order By: Relevance
“…Mitochondrial DNA analysis of local Chinese goat populations [35] revealed that they formed 4 haplogroups and the results were consistent with archeological and genetic studies. In addition, genetic characterization studies, which were performed using 30 microsatellites [36] reported that the populations, which were raised in northwest and southwest as two sets in accordance with their geographical regions, heaped up within themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA analysis of local Chinese goat populations [35] revealed that they formed 4 haplogroups and the results were consistent with archeological and genetic studies. In addition, genetic characterization studies, which were performed using 30 microsatellites [36] reported that the populations, which were raised in northwest and southwest as two sets in accordance with their geographical regions, heaped up within themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity of several types of Chinese goats has also been reported, including the Chinese dairy goat (Wang et al, 2015), goats indigenous to southwest China (Wei et al, 2014;Zhao et al, 2014), the black goat (Miao et al, 2015;Zhong et al, 2013), and the cashmere goat (Di et al, 2011;Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Wei et al (2014) China (Yuan, Cheng, & Zhou, 2012 increasing evidence has supported a common genetic pattern in domestic animals (Jin et al, 2012;Lai, Chen, Liu, & Yao, 2007;Liu et al, 2006;Wu et al, 2007) due to the restricted gene flow of livestock between goats as a result of the Hengduan Mountains (Wei et al, 2014). F I G U R E 1 Population average pairwise differences among the seven goat populations.…”
Section: Discussionmentioning
confidence: 99%